Rethinking Theatrical Documents in Shakespeare's England - Stern, Tiffany (Bloomsbury Academic, 2019)
This book is open access and available on www.bloomsburycollections.com. It is funded by Knowledge Unlatched. Rethinking Theatrical Documents brings together fifteen major scholars to analyse and theorise the documents, lost and found, that produced a play in Shakespeare's England. Showing how the playhouse frantically generated paratexts, it explores a rich variety of entangled documents, some known and some unknown: from before the play (drafts, casting lists, actors' parts); during the play (prologues, epilogues, title-boards); and after the play (playbooks, commonplace snippets, ballads) - though 'before', 'during' and 'after' intertwine in fascinating ways. By using collective intervention to rethink both theatre history and book history, it provides new ways of understanding plays critically, interpretatively, editorially, practically and textually.